Medium-Term Fiscal Multipliers during Protracted Recessions - Dell'Erba, Salvatore (IMF Working Papers; Working Paper ;, 2014)
The paper examines the consequences of fiscal consolidation in times of persistently low growth and high unemployment by estimating medium-term fiscal multipliers during protracted recessions (PR) in a sample of 17 OECD countries. Based on Jorda's (2005) local projection methodology, we find that cumulative fiscal multipliers related to output, employment and unemployment at five-year horizons are significantly above one during PR episodes. These results suggest that medium-term fiscal consolidation plans to reduce public debt burdens should proceed gradually if economic activity remains below trend for a prolonged period.